Validity of the running anaerobic sprint test for assessing anaerobic power and predicting short-distance performances - Zagatto, Alessandro M. [UNESP]; Beck, Wladimir R.; Gobatto, Claudio A. [UNESP] (Lippincott Williams & Wilkins, 2009)
Zagatto, AM, Beck, WR, and Gobatto, CA. Validity of the running anaerobic sprint test for assessing anaerobic power and predicting short-distance performances. J Strength Cond Res 23(6): 1820-1827, 2009-The purpose of this study was to investigate the reliability and validity of the running anaerobic sprint test (RAST) in anaerobic assessment and predicting short-distance performance. Forty members of the armed forces were recruited for this study (age 19.78 +/- 1.18 years; body mass 70.34 +/- 8.10 kg; height 1.76 +/- 0.53 m; body fat 15.30 +/- 5.65%). The RAST test was applied to six 35-meter maximal running performances with a 10-second recovery between each run; the peak power, mean power, and the fatigue index were measured. The study was divided in two stages. The first stage investigated the reliability of the RAST using a test-retest method; the second stage aimed to evaluate the validity of the RAST comparing the results with the Wingate test and running performances of 35, 50, 100, 200, and 400 m. There were not significant differences between test-retest scores in the first stage of the study (p > 0.05) and were found significant correlations between these variables (intraclass correlation coefficient congruent to 0.88). The RAST had significant correlations with the Wingate test (peak power r = 0.46; mean power r = 0.53; fatigue index r = 0.63) and 35, 50, 100, 200, and 400 m performances scores (p < 0.05). The advantage of using the RAST for measuring anaerobic power is that it allows for the execution of movements more specific to sporting events that use running as the principal style of locomotion, is easily applied and low cost, and due to its simplicity can easily be incorporated into routine training. We concluded that this procedure is reliable and valid, and can be used to measure running anaerobic power and predict short-distance performances.
Keywords: running test; anaerobic component; running performance; Wingate test; lactate